2014
DOI: 10.5005/jp-journals-10021-1255
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Nasopharyngeal Airway Dimensions in Class II Individuals using Cone-beam Computed Tomography

Abstract: Objectives:The aims of our study were to use cone-beam computed tomography (CBCT) to assess the dimensional changes in the nasopharyngeal soft-tissue characteristics in Indian patients with Class II malocclusion and to compare the results with patients with ideal occlusion. Materials and methods:A sample of 20 patients (10 girls, 10 boys) with Class II malocclusion due to true mandibular retrognathism was selected. None of the subjects had a history of upper airway disease, adenoidectomy, or pathology in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…(12) Meanwhile, in a study by Daniel et al. and a study by Chaturvedi et al, differences between sexes and pharyngeal airway dimensions were found 16,17 . An airflow test, nasoendoscope examination, nasal resistance measurements, lateral cephalometric examination, magnetic resonance, and threedimensional cone beam computed tomography can be used for the evaluation of pharyngeal airway dimensions and capacity.…”
Section: Discussionmentioning
confidence: 97%
“…(12) Meanwhile, in a study by Daniel et al. and a study by Chaturvedi et al, differences between sexes and pharyngeal airway dimensions were found 16,17 . An airflow test, nasoendoscope examination, nasal resistance measurements, lateral cephalometric examination, magnetic resonance, and threedimensional cone beam computed tomography can be used for the evaluation of pharyngeal airway dimensions and capacity.…”
Section: Discussionmentioning
confidence: 97%